Antenatal breast expression in women with diabetes: outcomes from a retrospective cohort study - Soltani Hora; Scott Alexandra MS (BMC, 2012)
Abstract Background Women with diabetes are sometimes advised to express breast milk antenatally to prepare for breastfeeding and to store colostrum for infant feeding in preventing or treating hypoglycaemia after the birth. The acceptability, risks and benefits of this practice have not been evaluated. This was aimed to investigate the pattern of antenatal breast expression uptake and its relationship with birth outcomes in women with diabetes. Methods This was part of a two year retrospective cohort study of pregnant women with diabetes (type 1, 2 and gestational diabetes) who gave birth during 2001-2003 in Derby Hospitals NHS Foundation Trust (n = 94). The information on the practice of antenatal breastfeeding expression and birth outcomes was collected via self-administered questionnaires and by examining maternity records. Results Thirty-seven percent of women (35/94) recalled that they were advised to express antenatally and 17% did (16/94). The mean gestational age at birth for women who hand-expressed was lower than that for those who did not (mean difference (MD) (95% confidence intervals (CI)): -1.2 (−2.4 to 0.04), p = 0.06). A higher proportion of babies from the antenatal expression group were admitted to special care baby units (SCBU) (MD (95% CI): 21% (−3.9 to 46.3). Conclusions Less than half the women who stated that they were advised to express, did so. There seems to be an indication that antenatal breast milk expression and lower gestational age at birth are associated. The trend of a higher rate of SCBU admission for babies from the breast milk expression group compared to those who did not express antenatally is of concern. An appropriately-powered randomised controlled trial is needed to determine the safety of this practice and its acceptability to women and health professionals before it can be recommended for implementation in practice.